Short Scales for the Assessment of Personality Traits: Development and Validation of the Portuguese Ten-Item Personality Inventory (TIPI) - Nunes, Andreia; Limpo, Teresa; Lima, César F.; Castro, São Luís (Frontiers in Psychology, 2018)
The importance of quickly assessing personality traits in many studies prompted the development of brief scales such as the Ten-Item Personality Inventory (TIPI), a measure of five personality traits (extraversion, agreeableness, conscientiousness, emotional stability, and openness). In the current study, we present the Portuguese version of TIPI and examine its psychometric properties, based on a sample of 333 Portuguese adults aged 18 to 65 years. The results revealed reliability coefficients similar to the original version ( .39 - .72), very good 4-week test-retest reliability (n = 81, rs > .71), expected factorial structure, high convergent validity with the Big-Five Inventory (rs > .60), and correlations with self-esteem, affect, and aggressiveness similar to those found with standard measures of personality traits. Overall, our findings suggest that the Portuguese TIPI is a reliable and valid alternative to longer measures: it offers a promising tool for research contexts in which the available time for personality assessment is highly limited.